Hubungan Sosialisasi Gender Di Lingkungan Teman Sebaya Dengan Persepsi Gender Siswa Sekolah Dasar - Amalia Nur Ramadhani; Amrin Ma'ruf (Jurnal Neo Societal, 2025)
This study aims to describe the relationship between socialization in the peer environment and the formation of gender perception in elementary school students. This study uses a survey method conducted in two elementary schools in Purbalingga, Central Java, which are located in suburban areas. The study population consisted of 80 students, and the sample used was a saturated sample of 100% of the total population. The results showed that the Kendall tau correlation value between the two variables was 0.40 with a significance level of 0.01. This value shows a significant positive relationship between socialization in the peer environment and the respondents' gender perception. Socialization in the peer environment is a significant factor in the formation of gender perception of elementary school students. Positive and open interactions among peers can improve students' understanding of gender, while limited or biased interactions can reinforce less progressive gender stereotypes. The conclusion of this study is that peers play an important role in the formation of gender perceptions of elementary school students, so educators and parents need to pay attention to social dynamics in peer groups as a strategy to foster a more equal and inclusive understanding of gender.